PENGARUH KOMPENSASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT MARUKI INTERNASIONAL INDONESIA MAKASSAR - Pramadanu, Ahmad; Syarifuddin, Syarifuddin (Jurnal Ekonomi : Journal of Economic, 2021)
Effective compensation can help companies motivate and attract employees to always improve their performance. Leadership is an important part in an organization or company to achieve all the performance targets set by the company. PT Maruki Internasional Indonesia has 241 employees, and with such a large number of employees good management is needed by the company, so as to create efficiency and effectiveness in achieving organizational goals. The purpose of this study was to analyze and determine whether compensation and leadership have an effect on employee performance at PT Maruki Internasional Indonesia Makassar.This study is a descriptive and causal research because this study aims to analyze the relationship between variables that describe the results of research using quantitative methods. The sampling technique used in this study is probability sampling with simple random sampling, because the number of population is known, then in determining the number of samples using the Slovin formula, with the results of the sample involving 71 respondents. The data analysis technique used descriptive analysis and multiple linear regression analysis.Based on the results of the descriptive analysis of the Compensation, Leadership and Employee Performance variables as a whole, the magnitude of the influence of Compensation and Leadership is 75.8% and the remaining 24.2% is influenced by other variables not examined in this study. Partially, compensation and leadership have a significant effect on employee performance at PT Maruki Internasional Indonesia Makassar. Keywords: Compensation, Leadership, Employee Performance